Indoor Air Quality assessment - case study at Menara Kerja Raya Kuala Lumpur - Isfanizam bin Ismail (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
Indoor Air Quality (IAQ) generally may be defined as the nature of air that affects the health of the occupants in the building. Poor IAQ in the office buildings has been found to be associated with lower productivity, higher absenteeism, higher spending in health insurance, and a higher rate of a compensation claim. This research sought to investigate on Indoor Air Quality (IAQ) condition of the platinum Green Building Index (GBI) certified green buildings known as Menara Kerja Raya in Malaysia using post-occupancy evaluation. Comparison of the IAQ assessment parameter which refer to Industry Code of Practice (ICOP) 2010 with what prescribed in GBI guideline also been made. The methodology adopted in the study involves the on-site measurement of nine (9) IAQ parameter at eleven (11) floors and seventy-four (74) points of sampling. Nine IAQ (9) parameter investigated were Temperature, Relative Humidity, Air Flow, Carbon Dioxide (CO2), Carbon Monoxide (CO), Formaldehyde, Total Volatile Organic Compound (TVOC), Respirable Particulate, and Ozone. The data collection were analysed according to ICOP 2010 requirement. In general, the findings show that IAQ conditions varies across floor level, and office spaces layout, however, most of the floor meet the requirements of available standards ICOP 2010. This result was anticipated as Menara Kerja Raya was a new facility and designed to meet green building criteria especially on building material, system, office equipment, furniture and finishes. Finally, the findings show IAQ requirement presently prescribed in Malaysia's GBI was sufficient as the most prescription in GBI indicated that major IAQ element in ICOP 2010 had taken into account. Improvement of the GBI prescription in GBI scheme for IAQ section was been identified and highlighted so that IAQ condition in green building can give ultimate comfort and healthy environment to occupants.